Prophylactic Intraoperative Nasolacrimal Duct Intubation in Surgical Treatment of Facial Fractures—Is There a Role? - Ryan Liang Wei Teoh; Pei Yuan Fong; Elijah Zhengyang Cai; Yan Lin Yap; Eileen Chor Hoong Hing; Han Jing Lee; Vigneswaran Nallathamby; Wei Chen Ong; Jane Lim; Gangadhara Sundar; Thiam Chye Lim (Archives of Plastic Surgery, 2022)
Nasolacrimal duct (NLD) damage is associated in the majority of type II and III naso-orbito-ethmoid (NOE) fractures.1 Our study aims to investigate the efficacy and safety of prophylactic NLD intubation in the setting of facial fractures, by comparing incidence of postoperative epiphora and wound infection. A retrospective matched control study was conducted on all patients with surgically treated facial fractures from 2008 to 2013 (n = 280) (IRB ref number: DSRB 2013/01198). Patients with the following fracture types were included: NOE (n = 16), frontal sinus (n = 2), Le Fort II/III (n = 8), and > 1 type (n = 48). All patients in this study were included with the intention to treat. The study group comprised patients who were intubated, while the control group patients were not intubated. Each group had 37 patients matched for age, gender, fracture type, and injury type. A single oculoplastic surgeon skilled in lacrimal surgery performed the procedure for all intubated patients. Patients with more severe and complex facial fractures were intubated with bicanalicular Crawford stents. Postoperative epiphora and infective complications (both facial wound and dacryocystitis) were assessed at 1, 3, 6, and 12 months. There was no significant difference in incidence of either postoperative epiphora (p = 0.152) or wound infection (p = 0.556) comparing both groups. Reduced incidence of postoperative epiphora in the study group is statistically not significant and does not support the need for prophylactic intubation. If radiographic evidence of NLD disruption or regurgitation seen on syringing on the NLD intraoperatively is present, intubation is safe and efficacious only if performed by an expert.